Validation of Animal Physiology Practice Guide Based on Skills of Science Process for University Student in Major Biology Universitas Negeri Padang - Fitri Arsih; Rahmadhani Fitri; Relsas Yogica (Bioeducation Journal, 2017)
This research aims to develop practice guide based on skills of science process to fix and improve the ability of university students keps in practicum ativity on animal physiology course. This research conducted by using model of development Plomp. Instrument that used in this research has validity by expert. Data analyzed through descriptive quantitive. This research has completed prototype in the form of animal physiology practice guide based on skills of science process. The research datas have been obtained data of result validation practice guide with the average value 88% categorized valid. It concluded that develop of animal physiology practice guide can be used as preguidece to run skills of science process on animal physiology course.